Yinchenhao Decoction Mitigates Cholestatic Liver Injury in Mice via Gut Microbiota Regulation and Activation of FXR-FGF15 Pathway - Weiwei Li; Doudou Huang; Zichen Luo; Ting Zhou; Ziwen Jin (Pharmaceuticals, 2025)
Objective: Yinchenhao decoction (YCHD), a classical herbal formula comprising Artemisia capillaris, Gardenia jasminoides, and Rheum palmatum, has been clinically used for over 1000 years to treat cholestasis. However, its mechanism of action remains undefined. This study aimed to elucidate YCHD’s therapeutic mechanisms against cholestasis, with a focus on the gut microbiota-mediated regulation of the farnesoid X receptor (FXR)–fibroblast growth factor 15 (FGF15) pathway. Methods: An alpha-naphthyl isothiocyanate (ANIT)-induced cholestasis mouse model was established. Mice received YCHD (3/9 g/kg) for 7 days. 16S rRNA sequencing, targeted LC/MS (bile acid (BA) quantification), untargeted GC/MS (fecal metabolite detection), qPCR/Western blot (FXR pathway analysis), fecal microbiota transplantation (FMT), and antibiotic depletion were employed to dissect the gut–liver axis interactions. Results: YCHD alleviated cholestatic liver injury by reducing serum biomarkers, restoring BA homeostasis via FXR-FGF15 activation, and suppressing hepatic Cyp7a1-mediated BA synthesis. It remodeled gut microbiota, enriched FXR-activating secondary BAs (CDCA, DCA, CA), and restored the intestinal barrier integrity. Antibiotic cocktail abolished YCHD’s efficacy, while FMT from YCHD-treated mice enhanced its therapeutic effects, confirming microbiota dependency. Conclusions: YCHD mitigates cholestasis through gut microbiota-driven FXR activation and direct hepatobiliary regulation. These findings bridge traditional medicine and modern pharmacology, highlighting microbiome modulation as a therapeutic strategy for cholestatic liver diseases.